The Role Of Real Work College (KKN) Students In The Field Of Education As A Form Of Service In Kedungjaya Village - Gian Fitralisma; Nur Alia Sumanti; Imas Trimayanti; Endah Budiastuti; Sifa Novianti; Dian Hidayat (SOCIRCLE : Journal Of Social Community Services, 2024)
This article discusses the role of students in the Community Service Program (KKN) in Kedungjaya Village, Kedawung District, Cirebon City. The aim of this research is to reveal and analyze the role of KKN students in educational development in Kedungjaya Village and the positive impacts produced. The results of the research show that STIE Cirebon Group 3 KKN students have a significant role in improving the quality of education in Kedungjaya Village. They are involved in helping as volunteer workers, providing tutoring, and providing learning facilities to the KOBER Anggrek PAUD. The positive impact can be seen in improving the quality of teaching, student learning motivation, and creating a positive learning environment. Even though there are challenges in implementing the KKN program, collaboration between students, government and village communities is important in village development efforts. The role of KKN students reflects relevance in the context of village development and plays a role in improving the welfare of local communities. The main suggestions are to improve student preparation before the KKN program, strengthen cooperation between various parties, and improve educational infrastructure in Kedungjaya village.